2018
DOI: 10.1002/bkcs.11640
|View full text |Cite
|
Sign up to set email alerts
|

Suspension Polymerization of Thermally Expandable Microspheres Using Cinnamonitrile and Diethyl Fumarate as Crosslinking Agents

Abstract: Thermally expandable microspheres (TEMs) were synthesized via suspension polymerization using acrylonitrile as the major monomer. Methyl methacrylate and methacrylonitrile were used as supporting co-monomers, and 1,4-butanediol dimethacrylate was used as a crosslinking agent. In addition, cinnamonitrile (CN) and diethyl fumarate (DEF) were investigated as monomers to improve the expansion performance of the TEMs. However, the expandability of the TEMs using CN was diminished. When TEMs were prepared with DEF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The specific expansion temperature could be measured only for Group 1~2 and Group 12~14. As shown in Table 1, the expansion temperature of Group 1~2 was around 120 C, while that of the Group 12~14 was approximately 112 C. This temperature was far below those in other studies, 19,28,35 which was beneficial for the utilization of TEMs in wood. As for other groups, the exact expansion temperature could not be evaluated exactly, and the expansion temperature ranges of 120~150 and 120~140 C were obtained for Group 3~11 and Group 15~23 respectively, because these TEMs expanded gradually during a long temperaturerising period rather than at a specific temperature immediately.…”
Section: Particle Diameters and Expansion Properties Of Temsmentioning
confidence: 68%
See 1 more Smart Citation
“…The specific expansion temperature could be measured only for Group 1~2 and Group 12~14. As shown in Table 1, the expansion temperature of Group 1~2 was around 120 C, while that of the Group 12~14 was approximately 112 C. This temperature was far below those in other studies, 19,28,35 which was beneficial for the utilization of TEMs in wood. As for other groups, the exact expansion temperature could not be evaluated exactly, and the expansion temperature ranges of 120~150 and 120~140 C were obtained for Group 3~11 and Group 15~23 respectively, because these TEMs expanded gradually during a long temperaturerising period rather than at a specific temperature immediately.…”
Section: Particle Diameters and Expansion Properties Of Temsmentioning
confidence: 68%
“…They found that once the content of cross‐linking agent increased, the TEMs with a harder shell and worse expansion properties would be produced. Moreover, Kim et al 28 prepared TEMs using dimethyl fumarate (DEF) as the cross‐linking agent, and reported that DEF could improve the expansion properties of TEMs.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In fundamental research, TEMs have seen application in many next-generation materials and devices, including adhesives, microfluidic pumps, sensors, biomedical devices, and other soft robots. [9][10][11][12][13][14] To actualize TEMs' potential to contribute to nextgeneration materials and manufacturing, both new TEM compositions and fundamental design parameters must be determined. 4,[15][16][17] To this end, our interest in soft actuation methods led us to initiate a set of experiments to determine whether we could (1) use a monomer and copolymer never before used to make TEMs; and (2) systematically modulate reagents and reaction parameters to create a microsphere with heightened expansion.…”
Section: Introductionmentioning
confidence: 99%
“…TEMs are prepared via suspension free-radical polymerization. Others have shown this process is amenable to a variety of monomers, 1,4,9,23 crosslinkers, 2,3,24 and blowing agents. 24,25 Likewise, the expansion properties of TEMs have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Therefore, thermally expandable microspheres are widely used as light-weight fillers to improve thermal insulation, sound insulation, and electrical insulation. 4 They are used as foaming agents for thermoplastic materials, 5 in coatings, in printing inks, in 3D wallpaper, in the textile industry to produce three-dimensional patterns, 6 in adhesives, 7 and in microfluidic pumps. 8 When the surface of microspheres is functionalized, they are used to prepare conductive thermally expandable microspheres.…”
Section: Introductionmentioning
confidence: 99%